Commercial law including company law and industrial law - Sen, Arun Kumar; Mitra, Jitendra Kumar; Mukherjee, Sakti, (ed.) (Calcutta : The World Press Pvt. Ltd., 1994)
Business
1995-09-25
Keywords: Commercial legislation; Industrial legislation; legilation